2006
DOI: 10.1038/nn1715
|View full text |Cite
|
Sign up to set email alerts
|

Control of microglial neurotoxicity by the fractalkine receptor

Abstract: Microglia, the resident inflammatory cells of the CNS, are the only CNS cells that express the fractalkine receptor (CX3CR1). Using three different in vivo models, we show that CX3CR1 deficiency dysregulates microglial responses, resulting in neurotoxicity. Following peripheral lipopolysaccharide injections, Cx3cr1-/- mice showed cell-autonomous microglial neurotoxicity. In a toxic model of Parkinson disease and a transgenic model of amyotrophic lateral sclerosis, Cx3cr1-/- mice showed more extensive neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

72
1,276
7
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,347 publications
(1,384 citation statements)
references
References 37 publications
72
1,276
7
7
Order By: Relevance
“…Dénes et al demonstrated that there were no significant changes in the ischemic brain damage between Cx3cr1 GFP/+ and wild type mice, and Saederup et al showed that monocyte/macrophage recruitment after thioglycollate‐induced peritonitis was not significantly changed between Cx3cr1 GFP/+ Ccr2 RFP/+ and wild type mice (Dénes et al, 2008; Saederup et al, 2010). Moreover, we showed that Cx3cr1‐GFP+ and Ccr2‐RFP+ cells overlapped completely with Iba1, a marker expressed in both resident microglia and blood‐derived macrophages, as reported previously (Cardona et al, 2006). Thus, we believe that this strain of mice can be used to investigate the contribution of resident microglia and blood‐derived macrophages after HI without influence of the transgene expression.…”
Section: Discussionsupporting
confidence: 89%
“…Dénes et al demonstrated that there were no significant changes in the ischemic brain damage between Cx3cr1 GFP/+ and wild type mice, and Saederup et al showed that monocyte/macrophage recruitment after thioglycollate‐induced peritonitis was not significantly changed between Cx3cr1 GFP/+ Ccr2 RFP/+ and wild type mice (Dénes et al, 2008; Saederup et al, 2010). Moreover, we showed that Cx3cr1‐GFP+ and Ccr2‐RFP+ cells overlapped completely with Iba1, a marker expressed in both resident microglia and blood‐derived macrophages, as reported previously (Cardona et al, 2006). Thus, we believe that this strain of mice can be used to investigate the contribution of resident microglia and blood‐derived macrophages after HI without influence of the transgene expression.…”
Section: Discussionsupporting
confidence: 89%
“…Astrocytes expressing GFAP or glutamine synthetase as well as neurons identified by NeuN expression were not positive to GFP in intact mice and in mice subjected to MCAo (not shown), confirming previous observations by others (Cardona et al, 2006).…”
Section: Gfp/cd45-staining Reveals Less-infiltrating Leukocytes In Thsupporting
confidence: 91%
“…Absence of fractalkine receptor in CX3CR1À/À mice was reported to cause cell-autonomous microglial neurotoxicity after systemic LPS treatment in a toxic model of Parkinson's disease and a transgenic model of amyotrophic lateral sclerosis (Cardona et al, 2006). Furthermore, CX3CR1À/À microglia were shown to accumulate and promote retinal degeneration (Combadiere et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that IL-1␤ develops neurotoxic properties in the brain. 5,13,32 However, in the retina IL-1␤ was shown to inhibit ganglion cell death, 6 and IL-1␤ substitution saved photoreceptors in light-induced models 7 and genetic retinal degeneration. 8 Here, we show that IL-1␤ is significantly induced in the light-induced model in albino rats ( Figure 4D) and in albino mice ( Figure 5B).…”
Section: Discussionmentioning
confidence: 99%